MENDETEKSI KECURANGAN LAPORAN KEUANGAN MENGGUNAKAN TEORI FRAUD HEXAGON - Nurbaiti , Annisa; Arthami, Azka (Faculty of Economics and Business University of Mataram, 2023)
This study aims to examine the effect of the hexagon fraud theory on fraudulent financial statements in the transportation and logistics sector in 2017 – 2021. This study uses a quantitative approach, with secondary data on company annual reports. A total of 60 samples were selected by purposive sampling and analyzed using panel data regression. The research findings show that pressure has a significant negative effect on fraudulent financial statements, while opportunity and rationalization have a significant positive effect on fraudulent financial statements. However, capability, arrogance, and collusion have no significant effect on fraudulent financial statements. The results of this study imply that the existence of pressure, opportunity, and rationalization on a person can indicate fraudulent financial reporting.